2013
DOI: 10.1002/jssc.201300813
|View full text |Cite
|
Sign up to set email alerts
|

Determination of asymmetric and symmetric dimethylarginines in human plasma by HPLC with electrochemical detection

Abstract: A new HPLC method was developed and validated for the determination of asymmetric and symmetric dimethylarginines and l-arginine in human plasma. After SPE and evaporation of the eluate, the samples were derivatised with an o-phthaldialdehyde reagent containing 3-mercaptopropionic acid. The derivatives formed were analysed by isocratic RP-HPLC with electrochemical detection at +320 mV. The mobile phase consisted of 50 mM phosphate buffer (pH 6.1) containing 10% v/v acetonitrile, the flow rate was 1 mL/min. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…To date, numerous methods have been utilized to purify nucleosides satisfactorily from a complex matrix of biological samples, such as urine, serum, blood, and even tissues [22,[24][25][26]. In our current study, we performed RP-HPLC analysis of ten different nucleosides in the urine, serum, blood, and even tissues and found that significantly increased levels of nucleosides were observed in the plasma and urine of gallbladder carcinoma patients.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…To date, numerous methods have been utilized to purify nucleosides satisfactorily from a complex matrix of biological samples, such as urine, serum, blood, and even tissues [22,[24][25][26]. In our current study, we performed RP-HPLC analysis of ten different nucleosides in the urine, serum, blood, and even tissues and found that significantly increased levels of nucleosides were observed in the plasma and urine of gallbladder carcinoma patients.…”
Section: Discussionmentioning
confidence: 86%
“…Because there are no specific enzymatic systems to incorporate modified nucleosides into the macromolecular nucleic acid, these nucleosides once released cannot be reutilized, nor are they further degraded, but are excreted into the urine . Other studies also have demonstrated that urinary nucleoside excretion is little affected by the diet in humans, and when normalized to urinary creatinine levels, the daily excretion rate of urinary nucleosides is remarkably constant in healthy individuals . Thus, nucleoside detection could be useful in the assessment of human diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their concentration level in the biological fluids can reflect the situation of RNA degradation. Thus, they can be used as a diagnostic tool for human cancers and other degenerative diseases . It is therefore important to develop efficient and practical methods for nucleoside enrichment from complex biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Existing methods for the determination of methylated arginines include electrophoresis , ion‐exchange chromatography , monoclonal antibody assays , HPLC–UV , and HPLC with electrochemical detection . Several recently reported techniques have significantly higher sensitivity than earlier methods: LC–MS , MS/MS , CE–MS , CE–LIF , and UHPLC–MS .…”
Section: Introductionmentioning
confidence: 99%